Identification of Ligularia Herbs Using the Complete Chloroplast Genome as a Super-Barcode - Chen, Xinlian; Zhou, Jianguo; Cui, Yingxian; Wang, Yu; Duan, Baozhong; Yao, Hui (Frontiers in Pharmacology, 2018)
More than 30 Ligularia Cass. (Asteraceae) species have long been used in folk medicine in China. Morphological features and common DNA regions are both not ideal to identify Ligularia species. As some Ligularia species contain pyrrolizidine alkaloids (PAs), which are hazardous to human and animal health and are involved in metabolic toxification in the liver, it is important to find a better way to distinguish these species. Here, we report complete chloroplast (CP) genomes of six Ligularia species, L. intermedia, L. jaluensis, L. mongolica, L. hodgsonii, L. veitchiana, and L. fischeri, obtained through high-throughput Illumina sequencing technology. These CP genomes showed typical circular tetramerous structure and their size ranges from 151,118 bp to 151,253 bp. The GC content of each CP genome is 37.5%. Every CP genome contains 134 genes, including 87 protein-coding genes, 37 tRNA genes, eight rRNA genes, and two pseudogenes (ycf1 and rps19). From the mVISTA, there were no potential coding or non-coding regions to distinguish these six Ligularia species, but the Maximum Likelihood (ML) tree of the six Ligularia species and other related species showed that the whole CP genome can be used as a super-barcode to identify these six Ligularia species. This study provides invaluable data for species identification, allowing for future studies on phylogenetic evolution and safe medical applications of Ligularia.